THE EFFECT OF INTERPROFESSIONAL COLLABORATION AND TRANSFORMATIONAL LEADERSHIP ON PATIENT SAFETY WITH WORK MOTIVATION AS INTERVENING VARIABLES - Rizkia, Dian Gema; Girsang, Andri J.; Kusumapradja, Rokiah; Hilmy, M. Reza; Pamungkas, Rian Adi; Dewi, Sandra (Kesatuan Press, 2022)
The purpose of this study was to obtain empirical evidence of the role of work motivation in mediating the relationship between interprofessional collaboration and transformational leadership on patient safety in inpatient installations using a cross-sectional study design. Moreover, make 250 inpatient installation nurses with civil servant status as the unit of analysis. The study's results prove that interprofessional collaboration and transformational leadership positively and significantly affect work motivation and patient safety. Work motivation has a positive and significant direct effect on patient safety, and work motivation has a positive role in mediating interprofessional collaboration and transformational leadership on patient safety. The importance of patient safety culture will be of value to hospital performance in patients' eyes so that maximum results are formed on implementing patient safety culture. Not only talking about the effectiveness of interprofessional collaboration and transformational leadership of the head of the room but the importance of implementing work motivation in the form of encouragement to nurses. Will create satisfaction that impacts the effectiveness of interprofessional collaboration and transformational leadership in improving patient safety culture in inpatient installations.